14-3-3 proteins: a family of versatile molecular regulators - Obsilová, V; Silhan, J; Boura, E; Teisinger, J; Obsil, T (Physiological research, 2008)
The 14-3-3 proteins are a family of acidic regulatory molecules found in all eukaryotes. 14-3-3 proteins function as molecular scaffolds by modulating the conformation of their binding partners. Through the functional modulation of a wide range of binding partners, 14-3-3 proteins are involved in many processes, including cell cycle regulation, metabolism control, apoptosis, and control of gene transcription. This minireview includes a short overview of 14-3-3 proteins and then focuses on their role in the regulation of two important binding partners: FOXO forkhead transcription factors and an enzyme tyrosine hydroxylase.
Keywords: 14-3-3 Proteins; Animals; Tyrosine 3-Monooxygenase; proteiny 14-3-3; Protein Structure, Quaternary; sekvence aminokyselin; vazba proteinů; lidé; Molecular Sequence Data; Amino Acid Sequence; forkhead transkripční faktory; tyrosin-3-monooxygenasa; Models, Molecular; molekulární sekvence - údaje; Forkhead Transcription Factors; molekulární modely; Protein Conformation; konzervovaná sekvence; Protein Isoforms; konformace proteinů; kvarterní struktura proteinů; protein - isoformy; zvířata; Protein Binding; Conserved Sequence; Humans